Revisited larval morphology of Thanatophilus rugosus (Coleoptera: Silphidae) - Novák, Martin; Jakubec, Pavel; Qubaiová, Jarin; Šuláková, Hana; Růžička, Jan (International journal of legal medicine, 2018)
Determination of insect species and their instars, occurring on human remains, is important information that allows us to use insects for estimation of postmortem interval and detect possible manipulation with the body. However, larvae of many common species can be identified only by molecular methods, which is not always possible. The instar determination is even more challenging, and qualitative characters that would allow a more precise identification are mostly unknown. Thanatophilus rugosus (Linnaeus, 1758) is a common necrophagous beetle in the whole Palaearctic region from Europe to Japan. The species is often encountered on corpses of large vertebrates including humans, and its potential to become a useful bioindicator for forensic entomology is therefore high. Adults can be easily distinguished from other species; however, larvae were never thoroughly described to allow species and instar identification. The aim of this study was to provide reliable morphological characters that would allow species and instar identification of T. rugosus larvae. The material for morphological study was obtained from rearing under controlled conditions (20 °C and 12:12 h of light/dark period), and specimens that were not studied morphologically were allowed to complete their development. Quantitative and qualitative morphological characters for instar and species identification are described and illustrated. Additionally, we report observations of biology and developmental length for all stages of the species.
Keywords: Morphology; brouci; soudní vědy; Larva; Larval instar identification; Thanatophilus rugosus; Animals; Microscopy, Electron, Scanning; Forensic entomology; optické zobrazování; zvířata; Forensic Sciences; mikroskopie elektronová rastrovací; Optical Imaging; Coleoptera; larva